Effect of Adding Insulin Glargine on Glycemic Control in Critically Ill Patients Admitted to Intensive Care Units: A Prospective Randomized Controlled Study - Nader ND; Hamishehkar H; Naghizadeh A; Shadvar K; Iranpour A; Sanaie S; Chang F; Mahmoodpoor A (Diabetes, Metabolic Syndrome and Obesity, 2020)
Nader D Nader,1 Hadi Hamishehkar,2 Abdolreza Naghizadeh,3 Kamran Shadvar,3 Afshin Iranpour,4 Sarvin Sanaie,5 Francis Chang,1 Ata Mahmoodpoor3 1State University of New York at Buffalo, Jacobs School of Medicine and Biomedical Sciences, Buffalo, NY, USA; 2Department of Clinical Pharmacy, Faculty of Pharmacy, Tabriz University of Medical Sciences, Tabriz, Iran; 3Department of Anesthesiology and Critical Care, Faculty of Medicine, Tabriz University of Medical Sciences, Tabriz, Iran; 4Al Garhoud Private Hospital, Dubai, United Arab Emirates; 5Neurosiences Research Center, Aging Research Institute, Tabriz University of Medical Sciences, Tabriz, IranCorrespondence: Ata MahmoodpoorAnesthesiology, Tabriz University of Medical Sciences, School of Medicine, Tabriz, IranEmail amahmoodpoor@yahoo.comObjective: We aimed to examine the effects of adding a longer-acting insulin glargine to existing glucose control on reducing blood-glucose fluctuations in an intensive care unit (ICU).Methods: A total of 110 patients randomly received adjuvant insulin glargine 15 IU/day (glargine) or placebo (control), in addition to daily infusion of insulin to maintain glucose levels at a target of 140– 180 mg/dL. End points were mean and variance of blood glucose and frequency of hypoglycemia, hyperglycemia, ICU stay, and mortality. Data were analyzed with repeated-measures ANOVA and Mann–Whitney U test.Results: Average daily glucose level was significantly less in the glargine group than controls (P< 0.0001), while there was no difference in daily variance in blood glucose between the two groups. The duration of glucose concentrations being within the target range was identical between the glargine and control groups (16.6± 4.9 vs 16.4± 4.6 hours/day, P=0.844) during the 7 days of admission. The frequency of hypoglycemia was greater in the glargine group and total duration of hyperglycemia (> 180 mg/dL) much longer among controls (P< 0.001). Similar mortality rates were observed in both groups, while ICU length of stay was 2 days shorter in the glargine group.Conclusion: Addition of insulin glargine to routine protocols more effectively reduces glucose levels and decreases incidence of hyperglycemic episodes and regular insulin usage. This adjustment may be associated with decreases in duration of ICU stay or increases in hypoglycemic events.Keywords: critically ill patients, dysglycemia, hyperglycemia, insulin glargine